Pro-Active Music Higher Degrees : Final Report: Promoting, Acting On and Evaluating Quality Teaching and Learning in Music Higher Degrees. - Harrison, Scott (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at Griffith University. This fellowship addresses an under-explored area of pedagogy within higher education: the form and quality of interactions between supervisors and students in the field of music. Engaging with Higher Degree Research (HDR) communities, it aimed to develop a sustained commitment within and between them to an informed approach to research education, in particular by optimising the nature and quality of interactions between supervisors, higher degree research students and their professional communities. The fellowship represents a foundation for improving the higher research and degree supervision process in music, reducing reliance on the master-apprentice model of research supervision, developing collaborative approaches to supervision and learning, and creating a new citizenry of music educators.